Kinetic study of removal of the dispersed blue 124 dye from water using avocado seed Fuerte variety as adsorbent - Gonzales-Condori, Elvis Gilmar; Conislla-Ibarra, Ada Danitza; Meza-Surco, Fiorella Yesica; Yucra Condori, Harry R.; Villanueva Salas, Ana María; Angulo Vargas, Sheyla J.; Choquenaira-Quispe, Celia (LACCEI, 2024)
Adsorption processes with biomaterials are an environmentally friendly technology that allows the removal of pollutants; on the other hand, it is known that different factors can alter the removal of pollutants. For this reason, the kinetics of removal of Disperse Blue 124 (DB-124) dye from water using Fuerte variety avocado seed waste as adsorbent was evaluated in the present research. The studies were carried out in batch adsorption systems. For this purpose, the effect of pH, adsorbent dosage, initial dye concentration and temperature on the removal kinetics were jointly evaluated. It was found that the best conditions of the adsorption process were at an initial DB-124 concentration of 200 mg/L, a dosage of 2 g/L, pH=2 and a temperature of 40 °C, achieving the removal of 87.64 % of the dye. The kinetic study was fit in all cases to a pseudo-second order model, which indicates that the adsorption process corresponds to a chemisorption. It was also found that the removal of DB-124 is favored at higher temperatures, which corresponds to an endothermic process. The present research may initiate future DB-124 adsorption studies in real environments using textile wastewater.